The Binding of Isaac in J.R.R. Tolkien and Stephen King - Selvén, Sebastian (Biblical interpretation, 2020)
This article investigates biblical reception in the works of two popular modern fantasy authors. It stages an intertextual dialogue between Genesis 22:1-19, “the binding of Isaac”, and two episodes, in Stephen King’s The Gunslinger and J.R.R. Tolkien’s The Return of the King. After presenting the dynamics of what happens to the biblical text in these two authors and the perspectives that come out, a hermeneutical reversal is then suggested, in which the modern stories are used to probe the biblical text. One can return to the Bible with questions culled from its later reception, in this case King and Tolkien. This article argues that the themes touched upon by the two authors are important and hermeneutically relevant ones, sometimes novel and sometimes contributions to exegetical debates that have been going on for centuries.